CHRONIC HEART DEFICIENCY AND PORTAL HYRETENSION WITH COMPLICATED OF ANTICOAGULANT THERAPY IN PATIENTS IMPORTANCE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Current during Bukhara region in the branch treated in patients with portal hypertension 36 people in total the patient treated in 21 of these patient’s chronic heart deficiency with came This is it anticoagulant treatment in patients take when you go complications extimals watching we went. [2,4,5] This is it from anticoagulant treatment in 10 of the patients after in the mine coagulogram in the analysis positive result received Kolgan in patients changes not observed.